Foreign Aid and Market-Liberalizing Reform - Heckelman, Jac C.; Knack, Stephen (2012)
Market-oriented economic policies have been strongly linked to faster rates of economic growth. Foreign aid is often provided in part to encourage market-oriented reforms. We analyse the impact of aid on market-liberalizing policy reform, correcting for its potential endogeneity. Results indicate that higher aid slowed reform over the 1980-2000 period, as measured by a broad index of policies. Disaggregating policy into five areas, aid is associated with slower reform in some policy areas but not in others. Disaggregating by decade, the adverse impact of aid on policy reform is much more pronounced for the 1980s than for the 1990s.